Review of the pregnancy outcome of mother with advanced maternal age in Hospital Sultanan Aminah, Johor Bahru From 2017-2018 - Ping, Tan Yi (2020)
Objective: To investigate the association between advanced maternal age and adverse pregnancy outcomes. Study method: A cross-sectional study comparing 239 advanced maternal age mother (≥35 years old) and a control group of 239 pregnant mothers aged 20–34, delivering at Hospital Sultanah Aminah in Johor from 2017 through 2018. Each of these groups was further analysed depending on parity (nulliparity and multiparity). Demographic background and pregnancy outcomes were compared between the groups. Result: The mean age of study group and Controls was 37.48 ± 2.226 years and 28.21 ± 3.610 years, respectively. Advanced maternal age was associated with higher parity and pre-existing medical illness. Advanced maternal age was significantly associated with higher incidence of anaemia. Those nulliparity mother with advanced maternal age had increased risk of exposure to lower Apgar scores (≤4 at 1 minute) by 14.75 compared to Controls. There were no significant differences between the two age groups in the incidences of other adverse obstetric outcomes and perinatal outcomes. Conclusion: We observed that maternal anaemia was associated with advanced maternal age and a low Apgar score at 1 minute is an independent risk factor for advanced maternal age nulliparity. Otherwise, this study demonstrated that the the reproduction beyond the age of 35 years is not associated with any significant maternal, delivery and perinatal complications. Overall, the study showed that the outcome of pregnancy with advanced maternal age is comparable to the control group.